(untitled) (MATEMATIKA, 2014)
Let d be a positive integer which is not a perfect square. In this paper, by using continued fraction expansion of √d, we ﬁnd fundamental solution of some Pell equation. Moreover, we get all positive integer solutions of some Pell equations in terms of generalized Fibonacci and Lucas sequences. Keywords : Pell Equations; Continued Fraction; Generalized Fibonacci and Lucas numbers 2010 Mathematics Subject Classiﬁcation 11A55; 11B37; 11B39; 11D55; 11D09; 11J70.